New insights into the oxidation behaviors of crude oils and their exothermic characteristics: Experimental study via simultaneous TGA/DSC. (1st May 2018) - Wang, Yanyong; Ren, Shaoran; Zhang, Liang; Deng, Junyu; Peng, Xiyi; Cheng, Haiqing
Highlights: The non-isothermal pyrolysis and oxidation behaviors of typical light and heavy oil are investigated. The exothermic characteristics of different oxidation reactions of the light and heavy crude are compared. The oxidation kinetics of different crudes from this study and relevant literatures have been compared. Abstract: Air injection process has been widely applied for the exploitation of light and heavy oil reservoirs due to air's free availability and large quantity. The thermal effect induced by the oxidation reactions usually plays an important role in enhancing oil recovery, and thus a better understanding of the oxidation behaviors of crudes and their exothermic characteristics can provide valuable insights into the thermal effect of air injection process. In this study, non-isothermal oxidation and pyrolysis experiments have been conducted via simultaneous TGA/DSC methods in order to compare the oxidation behaviors and exothermic characteristics of typical crude oils. The oxidation kinetics are obtained based on the experimental results and compared with those of other crudes from relevant literatures. The results show that, for the studied heavy oil, the reaction enthalpy of low temperature oxidation (LTO) reactions is comparable to that of the light oil, while the enthalpy of high temperature oxidation (HTO) reactions is about 2.5 times that of the light oil. In consideration of the enhanced oil recovery mechanisms induced by the thermal effect of LTO reactions in air injection process for light oil reservoirs, the LTO mechanism can also be applied for heavy oils to utilize the thermal effect, and air injection process in terms of HTO for heavy oils can be more pronounced in comparison with that for light oils. In addition, although the activation energy of HTO reactions is much higher than that of LTO reactions, the reaction rate of HTO can be much larger than that of LTO as a result of the relatively higher frequency factor and reaction temperature. Before the field implementation of an air injection project, proper reservoir screening (including reservoir temperature, pressure, oil saturation and the oxidation natures of targeted oil) as well as rational surface operation design (for a reasonable air injection rate) are needed to take advantage of the thermal effect for enhancing oil recovery.